Relationship Between Acute Appendicitis and Platelet Indices in Childhood - Asena Sucu; Orkun Tolunay; İlknur Banlı Cesur; Zerrin Özçelik; Tamer Çelik; Salim Reşitoğlu; Ümit Çelik (Galenos Yayinevi, 2018)
Introduction: Appendicitis is the inflammation of the appendix vermiformis. Clinical diagnosis of acute appendicitis in children is still a problem. Platelet indices, platelet distribution width and mean platelet volume have been evaluated for some infectious and inflammatory diseases. In this study, we aimed to investigate whether platelet distribution width values and mean platelet volume were decisive for the diagnosis of appendicitis in children. Methods: In our hospital, 504 pediatric patients who presented with acute abdomen and received the diagnosis of acute appendicitis between 2011 and 2016, and 106 children living in the same region, who attended the pediatric outpatient clinics for general follow-up, were included in the study. The patient and control groups were analyzed for gender, age, platelet count, platelet distribution width and mean platelet volume. A receiver operating characteristic (ROC) curve was drawn to describe the parameters that may be statistically significant. Results: There was a significant difference in platelet distribution width and mean platelet volume values between the two groups (p<0.001). The platelet distribution width values were higher and the mean platelet volume values were lower in appendicitis patients than in healthy children. The ROC curve analysis suggested a cut-off value of >14.3 fL for platelet distribution width for the diagnosis of appendicitis with a sensitivity, specificity, positive predictive value, and negative predictive value of 77.6%, 85.8%, 96.3%, and 44.6%, respectively. A cut-off value of <9.35 fL for mean platelet volume was used for the diagnosis of appendicitis with a sensitivity, specificity, positive predictive value, and negative predictive value of 78.1%, 81.1%, 95.2%, and 43.9%, respectively. Conclusion: Our results suggest that platelet distribution width and mean platelet volume may be used for the diagnosis of appendicitis in children with the sensitivity of at least 77.6% and 78.1%, respectively. Mean platelet volume and platelet distribution width, which can easily be investigated in complete blood count, may serve as markers for the diagnosis of appendicitis in children, however, further large-scale studies are needed.